Smart Factory Design: Integrating IoT for Better Industrial Management - Abdurahim Alfadel Sakeb; Abdullatif Mehemed Gohman; Abdussalam Ali Ahmed (African Journal of Advanced Pure and Applied Sciences, 2023)
In the era of Industry 4.0, the convergence of digital technologies with industrial processes has paved the way for the development of smart factories. These smart factories, which feature interconnected systems and advanced automation, have revolutionized industrial management by increasing operational efficiency, enabling real-time monitoring, and facilitating predictive maintenance. Central to the transformation of traditional manufacturing units into smart factories is the integration of the Internet of Things (IoT). In this paper, we provide an in-depth exploration of the role of IoT in smart factory design and its implications for industrial management, including improved asset utilization, predictive maintenance capabilities, and increased worker safety. It explores how sensor-equipped machinery, real-time data analytics, and cloud-based platforms synergize to create an interconnected ecosystem that improves production processes, increases operational efficiency, and can facilitate active decision-making. We discuss the key components of IoT-enabled smart factories, examine the benefits and challenges associated with adopting IoT in industrial settings, and present case studies highlighting successful implementations in various industries. We also identify future trends and innovations in the field and provide recommendations for organizations leveraging IoT for better industrial management.